Isolated Infundibular Pulmonary Stenosis in Adult (University Heart Journal, 2018)
Isolated infundibula pulmonary stenosis (UPS) in adult is an uncommon cardiac abnormality. Infundibula pulmonary stenosis leading to right ventricular hypertrophy is a big problem. Early excision of hypertrophied muscular band can overcome this problem. In our case report we have done excision of pulmonary infundibula muscle band of a late case of isolated pulmonary infundibula stenosis. And our patient showed a good response after excision of infundibula muscle band.University Heart Journal Vol. 13, No. 2, July 2017; 65-66